Land fragmentation, agricultural productivity and implications for agricultural investments in the Southern Agricultural Growth Corridor of Tanzania (SAGCOT) region, Tanzania - Kadigi, Reuben M.J.; Japhet, J. Kashaigili; Agnes, Sirima; Felix, Kamau; Anna, Sikira; Winfred, Mbungu (Academic Journals, 2017)
There are polarized evidences of the impact of agricultural land fragmentation on land productivity. On the one hand there viewpoints which consider land fragmentation to harm agricultural productivity. On the other hand there are counter thoughts which view land fragmentation as a positive situation which allows farmers to cultivate many environmental zones, minimise production risk and optimise the schedule for cropping activities. We use the case of Ihemi cluster in the Southern Agricultural Growth Corridor of Tanzania (SAGCOT) to investigate the impact of land fragmentation on crop productivity. We furthermore discuss the nature and causes of land fragmentation in the SAGCOT region and its implication on the future structure of agricultural landholdings and welfare of smallholder farmers in the region. The results showed that the nature and level of fragmentation in the study area were the outcome of combined, rather than isolated influences of supply and demand driven factors. Overall, the results did not support the claim that fragmentation reduces land productivity. This then implies that land fragmentation should not always be considered as defective. There were evidences of increasing chunks of land owned by rich farmers and investors which increased the possibility for increased consolidation of agricultural land under large scale farming. However, the landholdings for smallholder farmers might become increasingly more fragmented as poor smallholder farmers continue selling their land holdings to rich farmers and investors. Releasing the SAGCOT region’s potential for agricultural development will require that smallholder farmers are helped to secure adequate and suitable land for farming, raise agricultural productivity, diversify their sources of income, and adopt good production practices. This requires setting up a strong base of investor - farmer synergies for inclusive agricultural growth.